2012
DOI: 10.1128/aac.00713-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systemic Infection Induced by Pseudomonas aeruginosa on the Brain Uptake of Colistin in Mice

Abstract: In view of reports of colistin-induced neurotoxicity in infected patients, the aim of this study was to assess whether the integrity of the blood-brain barrier (BBB) and the brain uptake of colistin are altered in the presence of systemic Pseudomonas aeruginosa infection. Bacteremia was confirmed 8 h after intramuscular administration of P. aeruginosa ATCC 27853 to Swiss Outbred mice, at which time a single subcutaneous dose of colistin sulfate (40 mg/kg of body weight) or an intravenous dose of [ 14 C]sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Studies have demonstrated that direct administration of cytokines significantly enhances BBB permeability both in animals and in brain endothelial cell monolayers (10)(11)(12)(13)(14). However, in our previous studies involving inoculation of Pseudomonas aeruginosa to mice, despite significant increases in the plasma concentrations of the three above-mentioned cytokines, the BBB paracellular integrity was not compromised (15). These studies suggested a lack of correlation between the release of these three cytokines and BBB disruption.…”
mentioning
confidence: 39%
See 4 more Smart Citations
“…Studies have demonstrated that direct administration of cytokines significantly enhances BBB permeability both in animals and in brain endothelial cell monolayers (10)(11)(12)(13)(14). However, in our previous studies involving inoculation of Pseudomonas aeruginosa to mice, despite significant increases in the plasma concentrations of the three above-mentioned cytokines, the BBB paracellular integrity was not compromised (15). These studies suggested a lack of correlation between the release of these three cytokines and BBB disruption.…”
mentioning
confidence: 39%
“…In order to address whether the disparity resulted from the differences between the bacterial species, the effect of LPS from P. aeruginosa on BBB dynamics was assessed. After being administered in the same dosing regimen used for LPS from S. enterica (i.e., 3 mg/kg at 0, 6, and 24 h) (15), the brain uptake of [ 14 C]sucrose and colistin in mice treated with P. aeruginosa LPS was not different from that in saline-treated mice. In contrast, significantly higher […”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations